Reproductive efficiency methods and their relationship with siliqua production in Mustard - Islam, A; Fakir, MSA (Journal of the Bangladesh Agricultural University, 2013)
Five reproductive efficiency methods (REM) were evaluated under field condition to measure yield in 12 varieties of Brassica campestris L. in 2005 and 2006 at Mymensingh (24075? N latitude and 90050? E longitude) based on flower and siliqua production and total reproductive unit (TRU- number of buds, flowers, siliqua and number of empty pedicels). Five REMs were estimated and they were REM-I [ (Mature siliqua ÷ TRU) × 100]; REM-II [(Mature siliqua ÷ Flower number) × 100]; REM-III [(Mature siliqua + Immature siliqua) ÷ TRU × 100]; REM-IV[(Mature siliqua + Immature siliqua) ÷ Flower number ×100]; and REM-V [(Flower number ÷ TRU) × 100]. Siliqua number plant-1 showed positive and significant relationship with TRU (r=0.869** and 0.713** in 2005 and 2006, respectively) and flower number (r=0.984** and 0.834** in 2005 and 2006, respectively). Path analysis revealed that there exited high positive direct effect of siliqua number with sink (flower) number (0.655 and 0.714 in 2005 and 2006, respectively) and TRU (0.201 and 0.252 in 2005 and 2006, respectively). Among the REMs, REM-III had high positive direct effect with only siliqua production (1.331 and 0.899 in 2005 and 2006, respectively). For the first time we report REMs in mustard that number of sink production is an important index of siliqua yield and REM-III appears more reliable method of estimating RE in Brassica campestris. DOI: http://dx.doi.org/10.3329/jbau.v10i2.14715 J. Bangladesh Agril. Univ. 10(2): 223-228, 2012